Hypercomplex Analysis - Sabadini, Irene.; Shapiro, Michael.; Sommen, Frank. (Trends in Mathematics, 2009)
This book contains selected papers from the ISAAC conference 2007 and invited contributions. The topics covered represent the main streams of research in hypercomplex analysis as well as "state of the art" expository articles. The book will be of interest to researchers and postgraduate students in various areas of mathematical analysis, e.g. one and several complex variables; PDE; hypercomplex analysis; operator theory; theoretical and mathematics physics.